Metal/Metal‐Oxide Interfaces: How Metal Contacts Affect the Work Function and Band Structure of MoO3. (17th August 2012) - Greiner, Mark T.; Chai, Lily; Helander, Michael G.; Tang, Wing‐Man; Lu, Zheng‐Hong
Abstract When transition metal oxides are used in practical applications, such as organic electronics or heterogeneous catalysis, they often must be in contact with a metal. Metal contacts can affect an oxide's chemical and electronic properties within the first few nanometers of the contact, resulting in changes to an oxide's chemical reactivity, conductivity, and energy‐level alignment properties. These effects can alter an oxide's ability to perform its intended function. Thus, the choice of contacting metal becomes an important design consideration when tailoring the properties of transition‐metal oxide thin films or nanoparticles. Here, metal/metal‐oxide interfaces involving a widely used oxide in organic electronics, MoO3, are examined. It is demonstrated that metal contacts tend to reduce the Mo6+ cation to lower oxidation states and, consequently, alter MoO3's valence electronic structure and work function when the oxide layer is very thin (less than 10 nm). MoO3 becomes semimetallic and has a lower work function near metal contacts. The observed behavior is attributed to two causes: 1) charge transfer from the metal Fermi level into MoO3's low‐lying conduction band and 2) an oxidation‐reduction reaction between the metal and MoO3 that results in oxidation of the metal and reduction of MoO3. These results illustrate how interfaces are important to an oxide's ability to provide energy‐level alignment.